Membranous or Hypermobile Stapes Footplate: A New Anatomic Site Resulting in Third Window Syndrome - Gadre, Arun K.; Edwards, Ingrid R.; Baker, Vicky M.; Roof, Casey R. (Frontiers in Neurology, 2020)
Objectives: To describe an underappreciated pathology for posttraumatic persistent dizziness and third window syndrome as well as methods to diagnose and manage this disorder. Study Design: Observational analytic case studies review at a tertiary care medical center. Methods: Patients suffering persistent dizziness following head trauma and Tullio phenomena or Hennebert signs are included. All had normal otic capsules on high resolution temporal bone CT scans (CT). The gray-scale invert function was used to visualize the stapes footplate, and can be used to improve visualization of temporal bone anatomy and pathologic changes when diagnoses are in doubt. A search to check for the presence of perilymph leakage was performed in all cases. This was accomplished using intraoperative Valsalva maneuvers. Fat grafting of round and oval windows was performed. Results: Over an 11-year period between January 2009 and December 2019, 28 patients (33 ears) were treated. Follow-up with balance testing and audiograms were performed 6-8 weeks following surgery. Follow-up ranged from 6 months to 7 years. Prior to surgery all patients reported dizziness in response to loud sounds and/or barometric pressure changes. Seven out of 33 ears had demonstrable perilymph leakage into the middle ear; the rest (26 ears) appeared to have membranous or hypermobile stapes footplates. Membranous stapes footplates were better visualized using the invert function on CT. Thirteen patients had a fistula sign positive bilaterally while 15 had unilateral pathology. Twenty-four of the 28 patients (85.7%) showed both subjective and objective improvement following surgery. No patients suffered from a deterioration in hearing. Conclusions: A previously underappreciated membranous or hypermobile stapes footplate can occur following head trauma and can cause intractable dizziness typical of third window syndrome (TWS). Durable long term success can be achieved by utilizing fat graft patching of the round and oval windows. High resolution temporal bone CT scans using the gray-scale inversion (invert) function can assist in preoperative diagnosis. Key Words: head trauma, dizziness, vertigo, stapes footplate defect, hypermobile stapes, Tullio phenomenon, Hennebert sign, cVEMP, ocular tilt reaction, third window syndrome, perilymph fistula, fat grafts, gray-scale invert function CT scan Level of Evidence: 4